FINANCIAL INDICATORS OF COUNTRIES’ SECURITY DEVELOPMENT - Zakharova, O. V.; Marena, T. V.; Poberezhna, A. O. (The actual problems of regional economy development, 2024)
The article is devoted to the development of the methodic approaches to measuring the level of national economies security and analyzing the security situation, in particular, taking into account the impact of financial component on the parameters of countries’ secure development. Using the method of multidimensional analysis, the authors propose the algorithm for forming an integrated index of the country’s financial insecurity, the use of which allows to provide a comprehensive comparative analysis of national economies in terms of their financial security. The advantage of the proposed index is that it includes an information massive of financial indicators that are used in the practice of international analysis, and are open and accessible on the one hand, and have certain thresholds on the other. These indicators include public debt, external debt, state budget balance, official foreign exchange reserves, exchange rate changes, and the level of the shadow economy. The proposed financial insecurity index is a disincentive indicator, the growth of which indicates an increase in insecurity, and vice versa – a decrease in the index value identifies an increase in security and financial stability. The proposed index was tested on a sample of 11 countries, including EU countries (Romania, Bulgaria, Hungary, Czech Republic, Slovakia, Poland, Germany, France, Austria, and the Netherlands) and Ukraine for the period of 2016-2022. The results showed that Ukraine had the highest level of insecurity according to financial indicators (2.02 points in 2022), that is, a deviation from the critical values of more than 2 times. The lowest scores were obtained for Poland, the Czech Republic, and Bulgaria, that indicates a relatively secure state of their financial systems development. Based on the use of correlation and regression analysis and factor forecasting tools the level of financial insecurity of Ukraine for the period 2023-2025 was assessed, which will be of practical importance in terms of forming a system of measures to prevent possible risks or reduce the degree of their impact. In particular, it is determined that the state budget deficit, hryvnia exchange rate changes, the level of shadow economy and the level of public debt have a significant impact on the integrated financial insecurity index of Ukraine. For 2023, the financial insecurity index is estimated at 1.81, which is 10.5% lower than in 2022, indicating an increase in financial stability, but remains higher than 1, which means that the country is in a danger zone. For the periods of 2024 and 2025, the index will also increase by 5.3% and 2%, respectively, which is a signal of increased risks.